Некоторые закономерности макро-микроморфологии нервов надкостницы тазовых конечностей некоторых домашних млекопитающих - Павловский, Ю.А. (Вестник зоологии, 1972)
А study of total preparations of periosteum impregnated with silver nitrate showed that it has three types of nerve plexus: main, diffusive and concentrated. Each of the types has different forms of branching and the number of nerve elements in them is also unequal.